MANAJEMEN PEMBINAAN AGAMA ISLAM PADA WARGA BINAAAN DI LAPAS KELAS IIB KOTA SORONG - Rifai, Abd; Amin, Surahman; Sunatar, Bambang (Pascasarjana IAIN Sorong, 2023)
The objectives of this scientific research are: 1) To analyze the Management of Islamic Religious Development for Inmates in Class IIB Prisons in Sorong City. 2) To find out what the management pattern for developing Islamic character is for inmates in the Class IIB prison in Sorong City. This research uses descriptive qualitative research located in the Class IIB Prison in Sorong City. The approach in this research uses a qualitative descriptive approach. The primary data sources in this research are prisoners and prison guards and managers. Secondary data sources in this research are books, magazines, internet, reports and documentation. The data collection methods used were observation, interviews and documentation. Analysis of this research data through data reduction, data presentation and drawing conclusions. The results of the research show that: 1) Implementation of character education and Islamic religious guidance in the Class IIB Correctional Institution in Sorong City in collaboration with instructors from the Office of Religious Affairs, under the auspices of the Ministry of Religion for the City and Regency of Sorong. In carrying out their duties and obligations, both parties agreed to provide a series of routine activities to improve the spiritual aspects of prisoners. 2) The method used in the process of education and guidance of Islamic religious character is starting with reciting the Koran, then continuing with memorizing short letters and finally lectures or tausiah as well as questions and answers and 3) With collaboration with instructors from the Ministry of Religion providing something different from implemented in other prisons. Apart from that, the Correctional Institution also feels helped in providing Islamic religious services to prisoners. Some prisoners felt that it was very helpful, including increasing their knowledge of Islam.